2015
DOI: 10.1590/0103-8478cr20140625
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade da carcaça e rendimento de cortes suínos com o uso de ractopamina

Abstract: RESUMO O objetivo deste trabalho foi avaliar a influência do uso do aditivo ractopamina sobre os rendimentos dos cortes e a qualidade da carne suína (pH, cor, marmoreio e capacidade de retenção de água). Para os testes, foram utilizados

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 9 publications
0
3
1
1
Order By: Relevance
“…The modulation of energy metabolism by ractopamine, such as reduced lipogenesis and increased β-oxidation in muscle can improve the efficiency of energy use, increasing the energy available for muscle deposition. However, it can negatively impact IMF content (Reiter et al, 2007;Martins et al, 2015). However, in the present study ractopamine supplementation did not have a negative influence on IMF concentration.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…The modulation of energy metabolism by ractopamine, such as reduced lipogenesis and increased β-oxidation in muscle can improve the efficiency of energy use, increasing the energy available for muscle deposition. However, it can negatively impact IMF content (Reiter et al, 2007;Martins et al, 2015). However, in the present study ractopamine supplementation did not have a negative influence on IMF concentration.…”
Section: Discussioncontrasting
confidence: 66%
“…In skeletal muscle tissue, ractopamine stimulates protein synthesis (Adeola et al, 1992;Apple et al, 2007) and the increase in the proportion of glycolytic muscle fibers, allowing greater muscle hypertrophy (Gunawan et al, 2007;Almeida et al, 2015). However, ractopamine increases the use of fatty acids as energy source in muscle tissue, which may negatively impact pork IMF content (Reiter et al, 2007;Martins et al, 2015;.…”
Section: Introductionmentioning
confidence: 99%
“…Unexpectedly, Piau breed did not differ from the other genetic groups evaluated and demonstrated a good carcass yield despite presenting lower carcass quality. It is noteworthy that the carcass yield is given in terms of the relationship between the hot and cold carcass weight and body weight (Martins et al, 2015). Contrasting this result, Bertol et al (2013) reported higher hot carcass yields in Duroc pigs compared with a line composed mostly of Pietrain and naturalized Brazilian breeds being examined in a univariate way.…”
Section: Effects Of Genetic Group Nutritional Plan and Sex On Latent ...mentioning
confidence: 84%
“…Carcass yield involves not only the muscle quantity in carcass, as observed in most commercial cuts, but also fat, skin, and bones (Martins et al, 2015). Therefore, the factor carcass yield provides an evaluation of all these tissues simultaneously, and not only muscle tissue, although meat has the greatest market value.…”
Section: Multivariate Factor Analysismentioning
confidence: 99%
“…Entretanto, o consumo de carne in natura, seria maior caso fosse feita uma maior divulgação das propriedades nutricionais dos cortes. Os principais cortes suínos comercializados no mercado externo são pernil, paleta, lombo e sobrepaleta suínos (Martins et al, 2015). Mas apesar da grande demanda pelo produto brasileiro no exterior, a carne suína é ainda pouco consumida no Brasil, quando comparada à carne bovina e à carne de frango.…”
Section: Introductionunclassified